Challenges, attitudes and skills of occupational therapists towards pre-driving assessments practices in Malaysia - Lau, Yuan Hui; Hanif Farhan Mohd Rasdi,; Dzalani Harun,; Chang, Xun Yun (Penerbit Universiti Kebangsaan Malaysia, 2022)
A pre-driving assessment usually involves standardised and non-standardised tests to examine the skills for safe driving of people with disabilities. However, it is still unknown to what extent the pre-driving assessments are being practised among occupational therapists in Malaysia. Therefore, this study aims to investigate the association of challenges, attitudes, and skills of occupational therapists towards practising driving rehabilitation and explore the most used pre-driving assessment. A cross-sectional study had been conducted from July to September 2020. The convenient sampling method was used to recruit experienced occupational therapists in driving rehabilitation. A total of 53 therapists had completed an online survey. According to the results, the bivariate correlation between skills and challenges was positive and strong (rѕ = 0.680, p < 0.05). A multivariate analysis of variance (MANOVA) indicated that workplace variables had a significant effect on the combined dependent variables of challenges, attitudes, and skills, F(3,49) = 4.521 p = 0.007, partial Ƞ² = 0.217. This study found that the most used standardised assessment was the range of motion (n = 39, 73.6 %) and the right and left discrimination (n = 40, 75.5 %). The findings of this study identified that occupational therapists challenges and attitudes are significantly associated with the skills to practice driving rehabilitation. Malaysian occupational therapists working in the government sector reported better skills than those working in the private sector. Furthermore, numerous types of pre-driving assessments were used and vary from setting to setting. This study hopes to benefit occupational therapists and related rehabilitation practitioners towards a holistic understanding of Malaysia's driving rehabilitation practices.